(untitled) (Revista de História Regional, 2007)
The aim of this article is to analyze the relationship between the Brazilian Integralist Action (Ação Integralista Brasileira) and the press in Bahia, more precisely with the newspaper O Imparcial. This relationship reflected the political-ideological context of the decades of 1930 and 1940, which were marked by the rising of fascism, anticommunism and the anti-fascist fight. We tried to understand the position of the newspaper O Imparcial in face of the integralism in two different moments: the first phase, characterized by the adhesion to it, when the newspaper became the main way of spreading the integralist propaganda in Bahia in the 1930s, and the second phase, defined by the separation between the newspaper and the political movement, when it led a violent anti-integralist campaign in the first half of the 1940s; and we also analyze the political interests which oriented the editorial line of that newspaper in both phases .